Image Rejuvenation In The Digital Era: PT Bank Rakyat Indonesia (Persero) Tbk's Image Build And Develop Strategy In Winning Gen Z Loyalty - Arizal Fendy Pradana; Herdhani Nafisa; Cornellyo Andrea P; Pramudya Ibnu Subrata (CITACONOMIA, 2026)
This research is driven by the phenomenon of macroeconomic volatility in early 2026, triggered by the transition to the INDONIA interest rate as the sole benchmark replacing JIBOR. This dynamic created significant reputation risks and information asymmetry for the national banking sector, particularly for PT Bank Rakyat Indonesia (Persero) Tbk. This conceptual study aims to formulate a reconstruction of an adaptive financial communication and reputation management model to mitigate these risks while winning the loyalty of the new generation market. Using a qualitative descriptive approach through conceptual analysis based on Signaling Theory and Information Subsidies, the results indicate that BRI’s success lies in a strategic balance between building a new